The Contribution of Fine Sieve Fractions (63–150 μm) to Foraminiferal Abundance and Diversity in an Area of the Eastern Pacific Ocean Licensed for Polymetallic Nodule Exploration - Gooday, Andrew J.; Goineau, Aurélie (Frontiers in Marine Science, 2019)
The sieve mesh sizes used in benthic foraminiferal studies exert a strong influence on faunal densities and composition. We examined the consequences of including finer (63–150 µm) size classes in a study of Rose Bengal stained (‘live’) and dead foraminifera in 5 megacorer samples (0–1 cm layer) from abyssal sites in the eastern Clarion-Clipperton Zone (CCZ; equatorial Pacific), a region with commercially-significant deposits of polymetallic nodules. More than 60% of intact specimens originated from the finer (<150 µm ) fractions, with over half being picked from 63–125 µm residues. Test fragments, mainly agglutinated tubes, were also abundant but were more evenly distributed between coarser and finer residues. The two fractions yielded the same main groups (a mixture of formal taxa and informal groupings) and were dominated by single-chambered forms (‘monothalamids’), the majority undescribed. Some were disproportionately abundant in finer fractions: rotaliids in the stained (‘live’), textulariids in the dead, and trochamminids, Lagenammina spp., Nodellum-like forms, saccamminids and spheres in both assemblages. However, the most striking difference was the much greater abundance of tiny, largely undescribed spherical agglutinated morphotypes in the <150-µm fractions. Our 5 samples yielded 462 morphospecies, of which 313 occurred in <150-µm fraction and 170 were confined to this fraction. Twelve of the 31 top-ranked species in the stained assemblage were more or less limited (>90%) to the finer fractions; the corresponding number for the stained + dead assemblage was 12 out of 35. Of the 46 most abundant species in both assemblages combined, 35 were monothalamids (mainly spheres, Lagenammina spp., Nodellum-like forms, and saccamminids), the remainder being rotaliids (3), hormosinids (3), trochamminids (3) and textulariids (2). By far the most abundant species overall, a tiny agglutinated sphere, was almost entirely confined to the finer fractions. Although small foraminifera that pass through a 150-µm screen are time-consuming to analyse, they constitute an important part of abyssal Pacific assemblages and may include opportunistic species that respond to episodic food pulses as well as pioneer recolonisers of defaunated substrates. It is therefore important to consider them in studies of seabed mining impacts on abyssal benthic communities